Invisible marking system by extreme ultraviolet radiation: the new frontier for anti-counterfeiting tags. (6th July 2016) - Lazzaro, P. Di; Bollanti, S.; Flora, F.; Mezi, L.; Murra, D.; Torre, A.; Bonfigli, F.; Montereali, R.M.; Vincenti, M.A.
Abstract: We present a marking technology which uses extreme ultraviolet radiation to write invisible patterns on tags based on alkali fluoride thin films. The shape of the pattern is pre-determined by a mask (in the case of contact lithography) or by a suitable mirror (projection lithography). Tags marked using this method offer a much better protection against fakes than currently available anti-counterfeiting techniques. The complexity and cost of this technology can be tailored to the value of the good to be protected, leaving, on the other hand, the specific reading technique straightforward. So far, we have exploited our invisible marking to tag artworks, identity cards, electrical components, and containers of radioactive wastes. Advantages and limits of this technology are discussed in comparison with the anti-counterfeiting systems available in the market.